Measuring activities and participation in persons with haemophilia: A systematic review of commonly used instruments. Issue 2 (27th November 2017) - Timmer, M. A.; Gouw, S. C.; Feldman, B. M.; Zwagemaker, A.; de Kleijn, P.; Pisters, M. F.; Schutgens, R. E. G.; Blanchette, V.; Srivastava, A.; David, J. A.; Fischer, K.; van der Net, J.
Abstract : Introduction: Monitoring clinical outcome in persons with haemophilia (PWH) is essential in order to provide optimal treatment for individual patients and compare effectiveness of treatment strategies. Experience with measurement of activities and participation in haemophilia is limited and consensus on preferred tools is lacking. Aim: The aim of this study was to give a comprehensive overview of the measurement properties of a selection of commonly used tools developed to assess activities and participation in PWH. Methods: Electronic databases were searched for articles that reported on reliability, validity or responsiveness of predetermined measurement tools (5 self‐reported and 4 performance based measurement tools). Methodological quality of the studies was assessed according to the COSMIN checklist. Best evidence synthesis was used to summarize evidence on the measurement properties. Results: The search resulted in 3453 unique hits. Forty‐two articles were included. The self‐reported Haemophilia Acitivity List (HAL), Pediatric HAL (PedHAL) and the performance based Functional Independence Score in Haemophilia (FISH) were studied most extensively. Methodological quality of the studies was limited. Measurement error, cross‐cultural validity and responsiveness have been insufficiently evaluated. Conclusion: Albeit based on limited evidence, the measurement properties of the PedHAL, HAL and FISH are currently considered most satisfactory. Further research needs to focus on measurement error, responsiveness, interpretability and cross‐cultural validity of the self‐reported tools and validity of performance based tools which are able to assess limitations in sports and leisure activities.